An evaluation of the Barangay Disaster Coordinating Council of Barangay Pis-anan, Sibalom, Antique - Dador, Racy C (Miagao, Iloilo University of the Philippines in the Visayas, 2007)
The study sought to evaluate the Barnagay Disaster Coordinating Council of Barangay Pis-anan, Sibalom, Antique. It looked into the effectiveness of the BDCC in disaster management. The study also provides a description of the involvement of the different organizations in the operations of BDCC ; namely the Peoples Organizations, Private Individuals/Local Businessmen, and Government and Non-Government Agencies. it also looked into the economic and social effects of having an active BDCC. It was conducted using primary (FGD, KII and informal interviews) and secondary sources (journals and books) of information. A total of 10 respondents from the different staakeholders participated in the study. With these, the study was a combination of a participatory, descriptive, and exploratory research. The study also sought to jnow whether or not the Barangay Disaster Coordinating Council (BDCC) of Brgy. Pis-anan, Sibalom, Antique achieved its goal and objectives ; and has incorporated the Commnity-Based Disaster Management (CBDM) principles in their disaster management plans. Results showed that the BDCC of Barangay Pis-anan had incorporated the principles of CBDM in their disaster management activities. Almost all of their goals and objectives were achieved based on their barangay reports or annual reports.
Research Project (B.A. Community Development-Management) -- Miagao, Iloilo : U.P. in the Visayas, March 2007.